Ring opening metathesis polymerization (ROMP) of five‐ to eight‐membered cyclic olefins: Computational, thermodynamic, and experimental approach. Issue 18 (6th July 2017) - Hlil, Antsar R.; Balogh, Janos; Moncho, Salvador; Su, Haw‐Lih; Tuba, Robert; Brothers, Edward N.; Al‐Hashimi, Mohammed; Bazzi, Hassan S.
ABSTRACT: Ring opening metathesis polymerization (ROMP) of a series of low‐strain cyclic olefins and their hydroxyl derivatives using second generation Hoveyda–Grubbs catalyst has been investigated. Additionally, density functional theory (DFT) calculations were performed to evaluate the ring strain energies of the cyclic olefins and their hydroxyl derivatives, coupled with kinetic studies for the ROMP reactions. It was found that among different ring size monomers, Cy8 having a relatively moderate ring strain energy in comparison with the other cyclic olefins, exhibited the highest monomer conversion. The effect of temperature (0, 10, 15, and 25 °C) and monomer concentration (1 M; 2.5 M and 5 M forCy5 ; and 1 M and 5 M forCy7 ) for the cyclic olefinsCy5 andCy7 were investigated. In general, the experimental results for the kinetic ROMP studies obtained using complexHG2 correlate really well with the DFT calculations determined for the ring strain energies of the cyclic olefins. For comparison, DFT calculations predicted the following trend for the ring strain energiesCy8 > Cy5 > Cy7 > Cy6, and the polymerizations carried out experimentally followed the same trend in terms of monomer conversion, with the exception ofCy5 andCy7 at lower concentrations, which followed this trendCy8 > Cy7 > Cy5 > Cy6 . © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 3137–3145 Abstract : This study examines a series of cyclic olefins with different ring sizes for the ring opening metathesis polymerization reaction using a ruthenium catalyst.